Biological activity studies of Sensevieria hyacinthoides extracts (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
Biological activity was studied of the different solvent extracts such as n-hexane, ethyl acetate, n-butanol, and methanol extracts of the rhizomes of Sensevieria hyacinthoides. The cytotoxic potential were examined by using brine shrimp lethality bioassay. Ethyl acetate extract exhibited quite potent activity in brine shrimp lethality bioassay with LC50 1.95 μg/mL, respectively. These result suggested that it might contain antitumor or cytotoxic agent. The ethyl acetate extract showed significant free radical scavenging activity with IC50 10.51 μg/mL and demonstrated excellent antibacterial activity. The free radical scavenging activity of the solvent extracts (n-hexane, ethyl acetate and n-butanol) were assayed by using DPPH method. The IC50 for Vit-c (Ascorbic acid) and ethyl acetate extract were found to be 3.91 and 10.51 μg/mL, respectively.Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 15-20